The effect of fasudil on the uterine scar model created in rats: Uterine scar and fasudil - Yılmaz, Filiz; Aydemir, Selma; Cilaker Micili, Serap; Baykara, Basak; Yilmaz, Bayram (Journal of Surgery and Medicine, 2024)
Background/Aim: Uterine healing post-obstetric surgery is crucial for maintaining fertility. This study investigates if fasudil has a therapeutic impact on scars formed by a full-thickness incision in a rat’s uterus. Methods: We divided 21 female Wistar Albino rats randomly into three groups: control, scar, and treatment. The control group underwent no surgical procedure. We created a uterine scar model in the scar and treatment groups. For 30 days, the treatment group was intraperitoneally administered a single dose of 20 mg/kg/day fasudil dissolved in saline, while the control and scar groups were given saline. After these 30 days, all rats were sacrificed. We removed the right and left uterine horns from all groups. The left side was set aside for histological analysis, while the right side was used for ELISA analysis (alpha-SMA and TGF-beta). Results: The treatment group exhibited an increased uterine wall thickness compared to the scar group (P=0.03), although there was no discernible difference when compared with the control group. Both inflammation and fibrosis were notably higher in the scar group (P=0.01) but absent in both the treatment and control groups. The ELISA results, measuring alpha-SMA and TGF-beta, showed no statistically significant difference between the groups (P=0.321, P=0.375). Conclusion: Fasudil effectively reduced inflammation and fibrosis in our experimental rat model, hence preventing scar formation. We believe our study adds significant value to the existing literature by potentially expediting tissue regeneration.